2014
DOI: 10.1590/s1517-86922014000100016
|View full text |Cite
|
Sign up to set email alerts
|

Perfil funcional de atletas de basquetebol com traumatismo da medula espinal de acordo com a cif

Abstract: resumoIntrodução: A Classificação Internacional de Funcionalidade, Incapacidade e Saúde considera os múltiplos aspectos da funcionalidade; acredita-se que essa ferramenta possa contribuir para avaliar atletas com incapacidades. Objetivo: Determinar o perfil funcional de jogadores de basquete em cadeira de rodas de acordo com o core set da Classificação Internacional de Funcionalidade, Incapacidade e Saúde para indivíduos com traumatismo da medula espinal (TME). Métodos: Foi realizado um estudo transversal com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…In the present study no category showed a high level of disability, differently it was seen on another study (25), which considered a high level of disability in wheelchair basketball athletes with spinal cord injury, with more than 50% of participants rated by qualifiers 3 or 4. This low level of disability in present study can be interpreted as supervised aquatic and land-based exercises increase the abilities, or these limitations do not affect the practice of regular physical activity.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In the present study no category showed a high level of disability, differently it was seen on another study (25), which considered a high level of disability in wheelchair basketball athletes with spinal cord injury, with more than 50% of participants rated by qualifiers 3 or 4. This low level of disability in present study can be interpreted as supervised aquatic and land-based exercises increase the abilities, or these limitations do not affect the practice of regular physical activity.…”
Section: Discussioncontrasting
confidence: 76%
“…Similar to another study (25), the ICF considers not only the dysfunctions and disabilities of the person, but also the impact of these factors on social activities, as well as the influence of the environment, either as a facilitator or barrier to functional independence.…”
Section: Discussionmentioning
confidence: 99%